Persepsi Tentang Metode Service Learning, Konsep Diri dan Perilaku Prososial Mahasiswa - Cahyono, Yohanes Budi (Persona:Jurnal Psikologi Indonesia, 2016)
This study aims to test or not the relationship between the perceptions about the methods of Service-Learning and self concept with prosocial behavior in the students. Earlier predictions put forward in this study is there is a relationship between them.The selected subjects in this research are a student of Petra Christian University in Surabaya which are already taking courses with method of Service-Learning. Data retrieval done through measuring scale: 3 prososial behavior, perceptions about the methods of Service-Learningand self concept.At the time of data taken, item of prosocial behavior amounted to 106,item ofperceptions about Service-Learning method amounted 70 and item of self concept amounted 72 item. After analysis of the data done, item of prosocial behavior amounted49, item of perceptions about Service-Learning methods amountedto 55 and item of self concept amounted23. The data analysis done on a computerized program SPSS version 20 generates price R Â² = 0.768 level of significance 0.000. This means the variable perceptions about Service-Learning Method and variable self concept are jointly contributing to the significance of the relationship with the Prosocial Behavior of variable as much as 76.8%. Partially, the effective contribution of the variable perceptions about Service-Learning method of 73.93% and the variable self concept of 2.88%, while the remaining 23.2% is assumed to be derived from other variables that are not yet represented in this research.Keywords : prososial behavior, perceptions, service-learning, self-concept.